Wire Grid Moment Method (NEC) Models of a Patch Antenna - Elliot, P.G. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
Wire grid models of an air-loaded resonant circular patch antenna are used to calculate several observable quantities. The resonant frequency, input reactance, and bandwidth are accurately calculated, but the input resistance is underestimated by the grid models due to the existence of separate currents on both the top and bottom of the measured solid patch. The Lawrence Livermore (NEC3) Method of Moments computer program was used to generage the grid models. Averge wire lengths of about 0.03 wavelengths are required for accurate results. A comparison with other studies suggests that the 0.03 wavelength segmentation may be required because the patch is close to the ground plane (0.0175 wavelengths), and/or because errors in the near field calculation are compounded by the large fraction of energy stored in the near field since the patch is a high Q resonator.